CODESRIA Bulletin, No 2, 2018 - system, journal (CODESRIA Bulletin, 2019)
In this issue Editorial, Godwin Murunga and Divine Fuh 1 From the Executive Secretary’s Desk, Godwin Murunga 5 1. Place, Interest and Political Agency: Some Questions for Michael Neocosmos, Mahmood Mamdani 9 2. The Humbling of the All People’s Congress: Understanding the March 2018 Presidential Run-of Election Yusuf Bangura 17 3. Expanding the horizons of Transformation of Higher Education in Africa Dennis Masaka 24 4. Othering the Higher Education Sector in Governance and Democratic Processes in Africa Mlamuli N. Hlatshwayo & Kehdinga George Fomunyam 26 5. Addressing the Trilemma of Educational Trade-ofs on Africa’s Terrain for Sustainable Development Felix Kwabena Donkor, Tantoh Bikwibili Henry, Eromose Ebhuoma & Sylvi Fullard 29 6. The Introduction of the Subjects of Slavery and Slave Trade History in African Higher Education Curricula Paola Vargas Arana 32 7. The Emerging Erosion of Originality and Academic Writing Skills in Higher Education in Africa: The Boomerang Efects of Information Explosion M. H. A. Bolaji 34 8. Decolonising the Curriculum Andre Goodrich 41 9. Emergence of Local Language Film Production in Ghana Africanus Aveh 43 10. Sembene Meets Winnie Madikizela in After-Africa Okello Oculi 48